Examination of Accessibility for Disabled People at Metro Stations - Enginöz, Evren Burak; Şavlı, Hilal (My University, 2016)
According to World Health Organization (WHO), 10% of the population in developed countries and 12% of the population in developing countries are disabled people. And also researches by TUİK, in 2003, 12% of the population in our country are disabled. The problems that are faced in daily life, do not only affect disabled people but also their family. Therefore, it is said to be that half of our population have a disabled life. According to Scherrer, “Anyone, who has handicaps, is not a disabled person in an accessible place. But healthy person will become disabled in a place without accessibility.” (Scherrer 2001). Accessibility can be provided through the continuity of interrelated daily activities without any interruption. When the connection between the activities breaks off, we cannot mention about accessibility.
Keywords: Mimari; Ulaşılabilirlik; Engelli; Metro; Architecture; Accessibility; Disabled